STAGES OF INTRODUCTION OF ELECTRONIC GOVERNMENT - Mallaboev Nasirjon Murodullaevich; Qozaqova Munojat Sharifjanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Implementation of ICT in public administration consists of several stages. The first stage - the creation of web portals is characterized by the entry of the government into the electronic network structure. At this stage, the government has one or more sites that act as information providers. The site provides information to the public about the structure of the government, its ministers, agencies, etc. Information about phones, addresses, reception times, etc. will also be posted.